Two distinct effectors of the small GTPase Rab5 cooperate in endocytic membrane fusion. - Gournier, H (1998)
Using the yeast two-hybrid system, we have identified a novel 62 kDa coiled-coil protein that specifically interacts with the GTP-bound form of Rab5, a small GTPase that regulates membrane traffic in the early endocytic pathway. This protein shares 42% sequence identity with Rabaptin-5, a previously identified effector of Rab5, and we therefore named it Rabaptin-5beta. Like Rabaptin-5, Rabaptin-5beta displays heptad repeats characteristic of coiled-coil proteins and is recruited on the endosomal membrane by Rab5 in a GTP-dependent manner. However, Rabaptin-5beta has features that distinguish it from Rabaptin-5. The relative expression levels of the two proteins varies in different cell types. Rabaptin-5beta does not heterodimerize with Rabaptin-5, and forms a distinct complex with Rabex-5, the GDP/GTP exchange factor for Rab5. Immunodepletion of the Rabaptin-5beta complex from cytosol only partially inhibits early endosome fusion in vitro, whereas the additional depletion of the Rabaptin-5 complex has a stronger inhibitory effect. Fusion activity can mostly be recovered by addition of the Rabaptin-5 complex alone, but maximal fusion efficiency requires the presence of both Rabaptin-5 and Rabaptin-5beta complexes. Our results suggest that Rab5 binds to at least two distinct effectors which cooperate for optimal endocytic membrane docking and fusion.